Strengthening Shear Resistance of Beams without Web Reinforcements Using Vertical Prestressed Steel Bars - Zihui Liu; Yujun Cui; Weiqi Wang; Wei Cao; Xuan Wang; Xingwei Xue (Advances in Materials Science and Engineering)
Ensuring the shear capacity of concrete structures is crucial. The vertical prestressed steel bar (VPSB) strengthening method is effective for improving the shear behaviour of concrete structures. Four concrete beams are investigated to reveal the effect of VPSBs on the shear capacity of concrete beams without web reinforcement. Test results indicate that the shear capacity of the test beam strengthened by VPSBs in the beam is significantly increased by more than 95%, and the failure mode of the test beam changes from diagonal tension failure to shear compression failure. Additionally, the results provide insights into the strengthening mechanism of VPSBs, i.e., the shear contribution of the VPSBs can be categorised into two stages. The vertical compressive stress provides shear contribution in the first stage and provides control in terms of crack development; meanwhile, in the second stage, the stirrup action by VPSBs contributes to shear.